High-efficiency LOW-E photovoltaic glass containing fluorine selenium dioxide conductive film
By adopting a multi-layer composite structure with a fluorine-containing selenium dioxide conductive film and LOW-E coating on the photovoltaic glass, the difficulties of photovoltaic glass in taking into account high light transmittance and thermal insulation performance are solved, the effect of improving the efficiency and weather resistance of photovoltaic cells is achieved, and the production process is simplified.
Patent Information
- Application Number
- CN202411724568.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-11
AI Technical Summary
Existing photovoltaic glasses have difficulties in taking into account high light transmittance and good thermal insulation performance, and are complex in manufacturing processes, high cost, and insufficient weather resistance and long-term stability.
A multi-layer composite structure of fluorine-containing selenium dioxide conductive film and LOW-E coating is used to deposit the conductive film through chemical vapor deposition or sputtering technology, and a low-emissivity indium tin oxide or zinc oxide coating is deposited thereon to form a multi-layer structure.
It significantly improves the photoelectric conversion efficiency, thermal insulation performance and weather resistance of photovoltaic cells, reduces production costs, and maintains stable light transmittance and electrical conductivity during long-term use.
Smart Images

Figure HDA0005158874920000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic glass, and in particular to a high-efficiency LOW-E photovoltaic glass containing a fluorine-selenium dioxide conductive film. Background Art
[0002] As an important component of photovoltaic cells, the performance of photovoltaic glass directly affects the photoelectric conversion efficiency, stability and service life of the photovoltaic system. Therefore, how to improve the light transmittance, conductivity, thermal insulation and weather resistance of photovoltaic glass has become a hot topic in current photovoltaic glass technology research.
[0003] Traditional photovoltaic glass usually uses a single coating or conductive film, but these materials often cannot take into account both high light transmittance and good thermal insulation performance, resulting in photovoltaic glass being prone to problems such as reduced efficiency and material aging in high temperature environments. In order to solve this problem, in recent years, low-emissivity (LOW-E) coatings and conductive film technologies have gradually been applied to photovoltaic glass to improve its performance. LOW-E coatings improve the thermal insulation and weather resistance of photovoltaic glass by reducing thermal radiation and heat conduction; while conductive films promote charge collection in photovoltaic cells by increasing electrical conductivity. However, most of the conductive films and LOW-E coatings in the prior art have problems such as complex manufacturing processes, high material costs, and unstable performance, which limits their application in large-scale production.
[0004] Therefore, a new photovoltaic glass structure is urgently needed that can combine the advantages of conductive film and LOW-E coating, improve the photoelectric conversion efficiency, have good thermal insulation and weather resistance, and have a simple preparation process and low production cost. This is also the technical background and demand of the fluorine-containing selenium dioxide conductive film and LOW-E coating photovoltaic glass proposed in the present invention.
[0005] The photovoltaic glass on the market currently mainly uses single-layer or multi-layer transparent conductive films and thermal insulation coatings to improve the photoelectric conversion efficiency and thermal insulation performance. Typical photovoltaic glass technology includes the application of transparent conductive oxides such as indium tin oxide (ITO) and aluminum zinc oxide (AZO), which are deposited on the glass substrate by sputtering technology to improve the conductivity and transmittance of the glass. In addition, some products will add low-emissivity (Low-E) coatings, usually using metal materials such as silver (Ag) or aluminum (Al) to reduce thermal radiation and heat conduction, thereby improving the thermal insulation effect. However, the conductivity, transmittance and thermal insulation of these materials are usually difficult to take into account at the same time, and they are prone to performance degradation under high temperature or acid-base environments, affecting the long-term stability and life of the photovoltaic system.
[0006] The existing technology still has the following limitations:
[0007] 1. Limitations of the performance of the transparent conductive layer: Most photovoltaic glasses on the market use ITO or AZO as the transparent conductive layer. These materials have poor weather resistance under high temperature or harsh environments, which may lead to a decrease in conductivity during long-term use, affecting photovoltaic efficiency.
[0008] 2. The contradiction between heat insulation and light transmittance: Existing Low-E coatings usually use a single metal or metal oxide. Although they can reduce infrared radiation and heat conduction, it is difficult to maintain high light transmittance. It is easy to lose light transmittance in the visible light range, which affects the photoelectric conversion effect of photovoltaic cells.
[0009] 3. Insufficient long-term stability and weather resistance: The performance of current photovoltaic glass is easily degraded in harsh environments such as high humidity, high temperature, acid and alkali, which limits its life in outdoor applications. In addition, Low-E and conductive films are prone to delamination or oxidation under long-term exposure conditions, resulting in reduced thermal insulation and conductive properties.
[0010] 4. Complexity and high cost of the preparation process: The existing photovoltaic glass preparation process is complex, usually involving multiple sputtering and coating processes, high equipment costs, and low production efficiency, resulting in high costs during large-scale mass production and increasing the difficulty of application. Summary of the invention
[0011] In order to overcome the above-mentioned defects of the prior art, the present invention provides a high-efficiency LOW-E photovoltaic glass containing a fluorine-selenium dioxide conductive film to solve the problems raised in the background technology.
[0012] In order to achieve the above-mentioned purpose of the invention, the present invention provides a high-efficiency LOW-E photovoltaic glass containing a fluorine-containing selenium dioxide conductive film, wherein the photovoltaic glass includes a multi-layer composite structure, wherein the multi-layer composite structure includes a fluorine-containing selenium dioxide conductive film and a LOW-E coating, wherein the fluorine-containing selenium dioxide conductive film is arranged on a float glass, and the LOW-E coating is arranged on the fluorine-containing selenium dioxide conductive film.
[0013] Furthermore, the fluorine-containing selenium dioxide conductive film is deposited on the surface of the float glass by chemical vapor deposition or sputtering technology.
[0014] Furthermore, the method for preparing the fluorine-containing selenium dioxide conductive film comprises:
[0015] The fluorine-containing selenium dioxide conductive film is deposited on the pretreated float glass surface by chemical vapor deposition or magnetron sputtering technology. During the deposition process, the reaction chamber is first heated to above 400°C to ensure complete reaction of the gas, and the gas flow rate is controlled to maintain the stability of the deposition rate. The deposition time is at least 20 minutes. After completion, the float glass is gradually cooled to room temperature. The thickness of the fluorine-containing selenium dioxide conductive film is controlled by controlling the deposition time and the gas flow rate to ensure the thickness of the conductive film and ensure that it has good conductivity and transparency.
[0016] Furthermore, in the deposition of the fluorine-containing selenium dioxide conductive film, a mixed gas of sulfur hexafluoride and hydrogen selenide is used as a reaction gas, which can effectively provide a fluorine source and a selenium source, thereby ensuring the uniformity and stability of the conductive film.
[0017] Furthermore, the preparation method of the LOW-E coating includes:
[0018] On the deposited fluorine-containing selenium dioxide conductive film, a layer of indium tin oxide or zinc aluminum oxide coating with a thickness of 18 to 22 nm is deposited by magnetron sputtering technology. The coating has low emissivity and high transmittance, can effectively reduce thermal radiation and heat conduction, and improve the thermal insulation performance of photovoltaic glass. An intermediate layer is provided between the indium tin oxide or zinc aluminum oxide coating and the fluorine-containing selenium dioxide conductive film layer to form a LOW-E coating.
[0019] Furthermore, the intermediate layer is a titanium oxide or silicon dioxide layer.
[0020] Furthermore, the thickness of the fluorine-containing selenium dioxide conductive film is between 200 and 300 nm, and the thickness of the LOW-E coating is between 10 and 30 nm, so as to ensure the photoelectric conversion efficiency.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. High light transmittance and conductivity of the photovoltaic glass in this application: The conductive film can improve the transparency and conductivity of the glass and increase the photoelectric conversion efficiency of the photovoltaic cell by 3-5%;
[0023] 2. Thermal insulation performance of photovoltaic glass in this application: Low-E coating can effectively reduce thermal radiation and heat conduction, improve the thermal insulation performance of photovoltaic glass, reduce the efficiency drop caused by high temperature, and improve the overall efficiency by 2-3%;
[0024] 3. Weather resistance of photovoltaic glass in this application: fluorine-containing selenium dioxide conductive film and LOW-E coating have good chemical stability and weather resistance, can maintain stable performance in high temperature, high humidity, acid and alkali environment, and extend the service life of photovoltaic system by 2 to 3 times;
[0025] 4. The multi-layer composite structure of the photovoltaic glass in this application has a simple manufacturing process, which can be used for large-scale production and reduce production costs. The transmittance and conductivity of the photovoltaic glass in this application remain stable during long-term use, significantly improving the long-term stability and reliability of the photovoltaic system. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic structural diagram of an embodiment of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the invention, rather than all the embodiments. The embodiments of the present invention are described below in conjunction with the drawings.
[0028] The existing technology still has the following shortcomings:
[0029] 1. Limitations of the performance of the transparent conductive layer: Most photovoltaic glasses on the market use ITO or AZO as the transparent conductive layer. These materials have poor weather resistance under high temperature or harsh environments, which may lead to a decrease in conductivity during long-term use, affecting photovoltaic efficiency.
[0030] 2. The contradiction between heat insulation and light transmittance: Existing Low-E coatings usually use a single metal or metal oxide. Although they can reduce infrared radiation and heat conduction, it is difficult to maintain high light transmittance. It is easy to lose light transmittance in the visible light range, which affects the photoelectric conversion effect of photovoltaic cells.
[0031] 3. Insufficient long-term stability and weather resistance: The performance of current photovoltaic glass is easily degraded in harsh environments such as high humidity, high temperature, acid and alkali, which limits its life in outdoor applications. In addition, Low-E and conductive films are prone to delamination or oxidation under long-term exposure conditions, resulting in reduced thermal insulation and conductive properties.
[0032] 4. Complexity and high cost of the preparation process: The existing photovoltaic glass preparation process is complex, usually involving multiple sputtering and coating processes, high equipment costs, and low production efficiency, resulting in high costs during large-scale mass production and increasing the difficulty of application.
[0033] In order to solve the above problems, the present application provides a high-efficiency LOW-E photovoltaic glass containing a fluorine-containing selenium dioxide conductive film, by applying a fluorine-containing selenium dioxide conductive film 2 and a low-emissivity (LOW-E) coating on a float glass 1 to form a multi-layer composite structure, thereby significantly improving the photoelectric conversion efficiency, thermal insulation performance and weather resistance of photovoltaic cells, referring to Figure 1, the high-efficiency LOW-E photovoltaic glass includes a multi-layer composite structure, the multi-layer composite structure includes a fluorine-containing selenium dioxide conductive film 2 and a LOW-E coating 4, the fluorine-containing selenium dioxide conductive film 2 is arranged on the float glass 1, and the LOW-E coating 4 is arranged on the fluorine-containing selenium dioxide conductive film 2 to form a multi-layer composite structure. In order to ensure the high light transmittance and excellent electrical properties of the photovoltaic glass, the thickness of each layer needs to be accurately controlled during the preparation process. Specifically, the thickness of the fluorine-containing selenium dioxide conductive film 2 is 200-300nm, and the thickness of the LOW-E coating 4 is 10-30nm. The thickness and composition of each layer of material will be optimized according to experimental results and the needs of photovoltaic cells to obtain the best photoelectric conversion efficiency. In other implementations of this embodiment, the thickness of the fluorine-containing selenium dioxide conductive film 2 is 200nm or 300nm, or 250nm, and the thickness of the LOW-E coating 4 is 10nm or 30nm, or 25nm;
[0034] The fluorine-containing selenium dioxide conductive film 2 is deposited on the surface of the float glass 1 by chemical vapor deposition or sputtering technology. The fluorine-containing selenium dioxide conductive film has excellent transparency and conductivity, and also has good anti-reflection performance, and can improve the photoelectric conversion efficiency of the photovoltaic cell;
[0035] The preparation method of the fluorine-containing selenium dioxide conductive film 2 comprises:
[0036] The fluorine-containing selenium dioxide conductive film 2 is deposited on the surface of the pretreated float glass 1 by chemical vapor deposition or magnetron sputtering technology. During the deposition process, the reaction chamber is first heated to above 400°C to ensure that the gas reaction is complete, and the gas flow rate is controlled to maintain the stability of the deposition rate. The deposition time is at least 20 minutes. After completion, the float glass 1 is gradually cooled to room temperature. The thickness of the fluorine-containing selenium dioxide conductive film 2 is controlled by controlling the deposition time and the gas flow rate to ensure the thickness of the conductive film and ensure that it has good conductivity and transparency.
[0037] In the deposition of the fluorine-containing selenium dioxide conductive film 2, a mixed gas of sulfur hexafluoride and hydrogen selenide is used as a reaction gas, which can effectively provide a fluorine source and a selenium source, ensure the uniformity and stability of the conductive film, and select high-purity nitrogen (N2) for transmitting the reaction gas and ensuring the stability of the atmosphere in the reaction chamber;
[0038] The preparation method of the LOW-E coating 4 includes:
[0039] On the deposited fluorine-containing selenium dioxide conductive film 2, a layer of indium tin oxide or zinc aluminum oxide coating with a thickness of 18 to 22 nm is deposited by magnetron sputtering technology. The thickness of the indium tin oxide coating or the zinc aluminum oxide coating can be 18 nm or 22 nm, or 20 nm. In other implementations of this embodiment, the indium tin oxide coating and the zinc aluminum oxide coating can be deposited separately, and the total thickness of the two is between 18 and 22 nm. Different material combinations are selected according to the required performance requirements to ensure that the coating has high transmittance, low emissivity and good thermal insulation performance. The coating has low emissivity and high transmittance, can effectively reduce thermal radiation and heat conduction, and improve the thermal insulation performance of photovoltaic glass. An intermediate layer 3 is provided between the indium tin oxide or zinc aluminum oxide coating and the fluorine-containing selenium dioxide conductive film 2 to form a LOW-E coating 4. The thickness of the LOW-E coating 4 can be 20 nm or 30 nm, or 25 nm. The specific intermediate layer 3 is a titanium oxide or silicon dioxide layer to improve the adhesion and optical matching between the layers.
[0040] To ensure the high light transmittance and excellent electrical properties of photovoltaic glass, the thickness of each layer is precisely controlled during the preparation process. Specifically, the thickness of the conductive film is 200-300nm, and the thickness of the LOW-E coating 4 is 20-30nm. The thickness and composition of each layer of material will be optimized according to the experimental results and the needs of photovoltaic cells to obtain the best photoelectric conversion efficiency.
[0041] Optimization of optical and electrical properties: The optical properties of photovoltaic glass are optimized by adjusting the temperature, gas flow rate and deposition time during the deposition process. Experiments show that under this multilayer structure, the visible light transmittance of the glass can reach more than 90%, while it has a lower emissivity in the infrared band, ensuring efficient photoelectric conversion of photovoltaic cells.
[0042] Thermal insulation performance test: The thermal radiation conductivity test is used to evaluate the inhibitory effect of LOW-E coating 4 on heat transfer. The experimental results show that LOW-E coating 4 can significantly reduce thermal radiation, reducing the thermal conductivity of photovoltaic glass by about 30% to 50%, effectively improving its thermal insulation performance;
[0043] Compared with the prior art, the high-efficiency LOW-E photovoltaic glass of the fluorine-containing selenium dioxide conductive film 2 of the present invention has the following advantages:
[0044] 1. High light transmittance and conductivity of the photovoltaic glass in this application: The conductive film can improve the transparency and conductivity of the glass and increase the photoelectric conversion efficiency of the photovoltaic cell by 3-5%;
[0045] 2. Thermal insulation performance of photovoltaic glass in this application: LOW-E coating 4 can effectively reduce heat radiation and heat conduction, improve the thermal insulation performance of photovoltaic glass, reduce the efficiency drop caused by high temperature, and improve the overall efficiency by 2-3%;
[0046] 3. Weather resistance of the photovoltaic glass in this application: the fluorine-containing selenium dioxide conductive film 2 and the LOW-E coating 4 have good chemical stability and weather resistance, can maintain stable performance in high temperature, high humidity, acid and alkali environments, and extend the service life of the photovoltaic system by 2 to 3 times;
[0047] 4. The multi-layer composite structure of the photovoltaic glass in this application has a simple manufacturing process, which can be used for large-scale production and reduce production costs. The transmittance and conductivity of the photovoltaic glass in this application remain stable during long-term use, significantly improving the long-term stability and reliability of the photovoltaic system.
[0048] The technical solution of the present invention is described above in conjunction with specific implementation methods, but it should be noted that the above descriptions are only for explaining the solution of the present invention and cannot be interpreted in any way as a specific limitation on the scope of protection of the invention. Based on the explanation here, those skilled in the art can think of other specific implementation methods or equivalent replacements of the present invention without creative work, and they will all fall within the scope of protection of the present invention.
Claims
1. A high-efficiency LOW-E photovoltaic glass containing a fluorine selenium dioxide conductive film, characterized in that: The photovoltaic glass comprises a multi-layer composite structure, which comprises a fluorine-containing selenium dioxide conductive film and a LOW-E coating. The fluorine-containing selenium dioxide conductive film is arranged on the float glass, and the LOW-E coating is arranged on the fluorine-containing selenium dioxide conductive film.
2. The high-efficiency LOW-E photovoltaic glass containing fluorine selenium dioxide conductive film according to claim 1, characterized in that: The fluorine-containing selenium dioxide conductive film is deposited on the surface of the float glass by chemical vapor deposition or sputtering technology.
3. The high-efficiency LOW-E photovoltaic glass containing fluorine selenium dioxide conductive film according to claim 2, characterized in that: The preparation method of the fluorine-containing selenium dioxide conductive film comprises: The fluorine-containing selenium dioxide conductive film is deposited on the pretreated float glass surface by chemical vapor deposition or magnetron sputtering technology. During the deposition process, the reaction chamber is first heated to above 400°C to ensure complete reaction of the gas, and the gas flow rate is controlled to maintain the stability of the deposition rate. The deposition time is at least 20 minutes. After completion, the float glass is gradually cooled to room temperature. The thickness of the fluorine-containing selenium dioxide conductive film is controlled by controlling the deposition time and the gas flow rate to ensure the thickness of the conductive film and ensure that it has good conductivity and transparency.
4. The high-efficiency LOW-E photovoltaic glass containing fluorine selenium dioxide conductive film according to claim 3, characterized in that: In the deposition of the fluorine-containing selenium dioxide conductive film, a mixed gas of sulfur hexafluoride and hydrogen selenide is used as a reaction gas, which can effectively provide a fluorine source and a selenium source, thereby ensuring the uniformity and stability of the conductive film.
5. The high-efficiency LOW-E photovoltaic glass containing fluorine selenium dioxide conductive film according to claim 1, characterized in that: The preparation method of the LOW-E coating comprises: On the deposited fluorine-containing selenium dioxide conductive film, a layer of indium tin oxide or zinc aluminum oxide coating with a thickness of 18 to 22 nm is deposited by magnetron sputtering technology. The coating has low emissivity and high transmittance, can effectively reduce thermal radiation and heat conduction, and improve the thermal insulation performance of photovoltaic glass. An intermediate layer is provided between the indium tin oxide or zinc aluminum oxide coating and the fluorine-containing selenium dioxide conductive film layer to form a LOW-E coating.
6. The high-efficiency LOW-E photovoltaic glass containing fluorine selenium dioxide conductive film according to claim 5, characterized in that: The intermediate layer is a titanium oxide or silicon dioxide layer.
7. The high-efficiency LOW-E photovoltaic glass containing fluorine selenium dioxide conductive film according to claim 1, characterized in that: The thickness of the fluorine-containing selenium dioxide conductive film is between 200 and 300 nm, and the thickness of the LOW-E coating is between 10 and 30 nm, so as to ensure the photoelectric conversion efficiency.
Citation Information
Patent Citations
Temperable high-transparency and low-radiation coated glass and manufacturing method thereof
CN106431012A
Fluorine-containing conductive films
CN106471154A
Photovoltaic glass
CN108511545A
Method for preparing transparent conducting film with high photoelectric stability through magnetron sputtering
CN111593310A
Glass substrate with film and method for producing same
CN115093128A